Aerobic exercise and aerobic fitness level do not modify motor learning - Hung, Andrea (Sci Rep, 2021)
Motor learning may be enhanced when a single session of aerobic exercise is performed immediately before or after motor skill practice. Most research to date has focused on aerobically trained (AT) individuals, but it is unknown if aerobically untrained (AU) individuals would equally benefit. We aimed to: (a) replicate previous studies and determine the effect of rest (REST) versus exercise (EXE) on motor skill retention, and (b) explore the effect of aerobic fitness level (AU, AT), assessed by peak oxygen uptake (VO(2)peak), on motor skill retention after exercise. Forty-four participants (20–29 years) practiced a visuomotor tracking task (acquisition), immediately followed by 25-min of high-intensity cycling or rest. Twenty-four hours after acquisition, participants completed a motor skill retention test. REST and EXE groups significantly improved motor skill performance during acquisition [F(3.17, 133.22) = 269.13, P = 0.001], but had no group differences in motor skill retention across time. AU-exercise (VO(2)peak = 31.6 ± 4.2 ml kg(−1) min(−1)) and AT-exercise (VO(2)peak = 51.5 ± 7.6 ml kg(−1) min(−1)) groups significantly improved motor skill performance during acquisition [F(3.07, 61.44) = 155.95, P = 0.001], but had no group differences in motor skill retention across time. Therefore, exercise or aerobic fitness level did not modify motor skill retention.